Effectiveness of Methanol and Petroleum Benzene Extracts of Catharantus roseus Leaves in Reducing Blood Sugar Levels in Mice (Mus musculus) Diabetes Mellitus Model - Winda Siscawati; Chomsa Dintasari Umi Baszary (Pattimura University, 2025)
Catharanthus roseus, a plant belonging to the Apocynaceae family, contains various chemical compounds. The roots, stems, leaves, and seeds of Catharanthus roseus contain over 70 types of alkaloids, including 28 bi-indole alkaloids found throughout the plant. These compounds, many of which are beneficial in medicine, exhibit blood sugar-lowering (hypoglycemic) properties. This study aims to evaluate the effects of pure methanol extracts of Catharanthus roseus leaves on diabetes mellitus in mice, providing comprehensive evidence of its efficacy. Methanol and petroleum benzene extracts of Catharanthus roseus leaves were diluted to a 5% concentration and administered to test animals at a dose of 1.5 ml. After a two-week testing period, the results showed a significant reduction in blood sugar levels in the diabetes mellitus model mice. This demonstrates the hypoglycemic effect of methanol and petroleum benzene extracts of Catharanthus roseus leaves in lowering blood glucose levels in streptozotocin-induced mice.